A study of Michelangelo's David from an accountability perspective: Antecedents of dialogic accounting in the early Florentine Renaissance. (February 2023) - Manetti, Giacomo; Bellucci, Marco; Nitti, Carmela; Bagnoli, Luca
This article contributes to the accounting history literature through an investigation of the realisation and placement of Michelangelo's David from an accountability perspective. Using a contextual approach to thematic archival research, we explore whether and how early dialogic accounting (DA) tools were adopted by a hybrid organisation – the Opera of Santa Maria del Fiore in Florence – during the period of the statute of David's realisation (1501−1504). Through our analysis of primary and secondary sources, this study sheds light on an early Renaissance accountability system that was based on consensus building and DA. The novel contribution of this study is thus threefold. First, this article adds an early Renaissance analysis to the literature concerning DA. Second, we reveal a new strand of research for accounting historians in regard to the historical period and context of this study. Third, we extend the literature's focus to a hybrid organisation that was financed by the Republic of Florence, associated with the Church and managed by commercial guilds.